Scanning Probe Microscopy Atomic Force Microscopy and Scanning Tunneling Microscopy - Voigtländer, Bert. (NanoScience and Technology, 2015)
This book explains the operating principles of atomic force microscopy and scanning tunneling microscopy. The aim of this book is to enable the reader to operate a scanning probe microscope successfully and understand the data obtained with the microscope. The chapters on the scanning probe techniques are complemented by the chapters on fundamentals and important technical aspects. This textbook is primarily aimed at graduate students from physics, materials science, chemistry, nanoscience and engineering, as well as researchers new to the field.